MoS2 Thin Films for Photo-Voltaic Applications - Ramos Murillo, Manuel Antonio (Intech Open, 2019)
The low dimensional chalcogenide materials with high band gap of ~1.8 eV, specially molybdenum di-sulfide (MoS2), have been brought much attention in the material science community for their usage as semiconducting materials to fabricate low scaled electronic devices with high throughput and reliability, this includes also photovoltaic applications. In this chapter, experimental data for MoS2 material towards developing the next generation of high-efficiency solar cells is presented, which includes fabrication of ~100 nm homogeneous thin film over silicon di-oxide (SiO2) by using radio frequency sputtering at 275 W at high vacuum~10−9 from commercial MoS2 99.9% purity target. The films were studied by means of scanning and transmission electron microscopy with energy disperse spectroscopy, grazing incident low angle x-ray scattering, Raman spectroscopy, atomic force microscopy, atom probe tomography, electrical transport using four-point probe resistivity measurement as well mechanical properties utilizing nano-indentation with continuous stiffness mode (CSM) approach. The experimental results indicate a vertical growth direction at (101)-MoS2 crystallites with stacking values of 7-laminates along the (002)-basal plane; principal Raman vibrations at E12g at 378 cm−1 and A1g at 407 cm−1. The hardness and elastic modulus values of H = 10.5 ± 0.1 GPa and E = 136 ± 2 GPa were estimated by CSM method from 0 to 90 nm of indenter penetration; as well transport measurements from −3.5 V to +3.5 V indicating linear Ohmic behavior.